القاضي عياض ومنهجه في دراسة الحديث الشريف: "كتاب بغية الرائد لما تضمّن حديث أم زرع من الفوائد" نموذجا: Al-Qāḍī ʻIyāḍ and His Method in Studying the Noble Hadith: “A Book with Bughyah Al-Ra’id Lima Tadammanahu Hadith Ummi Zar’ min al-Fawa’id The Pioneer Endeavour for Benefits in Ummi Zar’s Report”: As an Example - Riahi Mohamed Kais; Mohammed Abullais Shamsuddin Mohammed Yaqub; Mohammed Farid Ali (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص يعتبر شرح القاضي عياض لحديث أم زرع من أنفس الشروحات والمعتمد من قبل العلماء والدارسين الأولين والمتأخرين. ويهدف هذا البحث إلى بيان المنهج الذي وظفه القاضي عياض في دراسة الحديث الشريف من خلال شرحه "بغية الرائد لما تضمّن حديث أم زرع من الفوائد". وقد اعتمد الباحث على المنهج الاستقرائي في التعريف بالقاضي عياض وجهوده في هذا الشرح، والمنهج التحليلي من أجل إبراز منهجية القاضي المبتكرة، التي ميزت هذا الشرح عن غيره. وتوصل البحث إلى أن القاضي عياض قد أسس لقواعد منهج جديد في التعامل مع النص الديني، يقوم على الشمولية والتكامل، وهو ما يفسر استخراجه لكم هائل من المسائل الفقهية والعربية، مع تحقيقات فريدة وإشارات بديعة. Abstract Al-Qāḍī ʻIyāḍ’s explanation of the hadith of Ummi Zara’ is considered one of the most authentic explanations and was approved by the early and later scholars. The aim of this research is to clarify the method employed by Al-Qāḍī ʻIyāḍ in the study of the noble hadith through his explanation “Bughyah al-Ra’id Lima Tadammanahu Hadith Ummi Zar’ min al-Fawa’id”. The researcher relied on the inductive approach in introducing Al-Qāḍī ʻIyāḍ and his efforts in this explanation, and the analytical approach in order to highlight Al-Qāḍī ʻIyāḍ’s innovative methodology, which distinguished this explanation from others. The research concluded that Al-Qāḍī ʻIyāḍ established the rules of a new approach in dealing with the religious text, based on comprehensiveness and integration, which explains his extraction of a huge number of jurisprudential and Arabic issues, with unique investigations and wonderful references.